2019
DOI: 10.1590/1983-1447.2019.20180032
|View full text |Cite
|
Sign up to set email alerts
|

Predição de risco e acurácia diagnóstica em pacientes internados com insuficiência cardíaca descompensada: estudo de coorte

Abstract: Resumo OBJETIVOS Analisar a acurácia diagnóstica de enfermagem em pacientes com predição de risco de piora clínica durante internação por insuficiência cardíaca agudamente descompensada. MÉTODO Estudo de coorte com coleta de dados em prontuário de acordo com o Acute Decompensated Heart Failure National Registry risk model. Após a definição dos pacientes em risco, aplicou-se a Escala de Acurácia de Diagnósticos de Enfermagem versão 2. A escala classifica a acurácia em nula, baixa, moderada ou alta. RESULTADO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In this regard, it is understood the interrelationship between these phenomena in the person with heart failure, as well as the necessary interventions in this process, as evidenced in several studies in the area (16)(17)(18) . The identification of such phenomena must be carried out based on the monitoring of changes in signs, such as respiratory and heart rate, peripheral oxygen saturation, expectoration, murmurs, noises or other signs, the positioning of people with an elevated headboard and oxygen therapy (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is understood the interrelationship between these phenomena in the person with heart failure, as well as the necessary interventions in this process, as evidenced in several studies in the area (16)(17)(18) . The identification of such phenomena must be carried out based on the monitoring of changes in signs, such as respiratory and heart rate, peripheral oxygen saturation, expectoration, murmurs, noises or other signs, the positioning of people with an elevated headboard and oxygen therapy (16) .…”
Section: Discussionmentioning
confidence: 99%
“…DCO was considered the priority diagnosis in several studies ( 30 - 32 ) . Other international ( 21 , 23 , 28 ) and national studies have identified DCO as one of the most prevalent diagnoses in people hospitalized with HF ( 20 , 27 , 29 , 35 , 42 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of highly accurate NDs is extremely important for clinical practice. A study proved that the implementation of intervals for high‐accuracy ND decreased the predictors of clinical worsening in patients with heart failure (Ernandes et al., 2019). In addition to the identification of high‐accuracy NDs, nurses must prioritize the diagnoses that will become the basis for nursing interventions.…”
Section: Discussionmentioning
confidence: 99%